Fruitful networks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Caribbean regional networking system for agriculture, science and technology (Procicaribe) has launched two new sub-networks; the Caribbean Roots and Tubers Network (CAROT) launched in September 2001 in Dominica and the Caribbean Vegetable...